QUESTIONING THE POSITION AND STATUS OF IBN TAIMIYYAH IN THE HANBALI SCHOOL OF THOUGHT - Badrus Samsul Fata; Imam Malik Riduan (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2022)
For centuries, polemic over Ibnu Taimiyyah (661-728H) has generated cross-generational tension among supporters and opponents. Those supporters believed Ibn Taimiyyah to be ma'shum,surpassed Imam Ahmad bin Hanbal, and unilaterally ordained him as khatim al-mujtahidin. A claim which ignores Sunnis scholars’ epistemic criticism across the school of thought and generations, including a critical assessment of the internal Hanbali school of thought itself. Such as Ibn Rajab (736-795H); Ibn al-Mardawi (817-885H); Ibn Najjar (898-972H); al-Buhuti (1000-1051H); and al-Safaraini (1114-1188H). By employing the interdisciplinary approach to analyzing the primary sources, the result of the study revealed that one of the internal consensuses of the Hanbali school of thought is clear enough. When there is a dispute over the results of tarjihformulation in ushuland furu', the hierarchy of the referential authority is as the following; first,Imam Ahmad bin Hanbal; second, Ibnu Qudamah al-Maqdisi al-Hanbali; third,Al-Majd al-Din Abi al-Barakat al-Taimi; fourth,Ibn Muflih al-Hanbali; fifth,Ibnu Rajab al-Hanbali; sixth,Ibnu Hamdan al-Hanbali; seventh,Taqiyy al-Din Ibn Taimiyyah; and eighth,Ibn ‘Abdus al-Hanbali. Considering its various controversies, the leading scholars of the Hanbali school of thought positioned Ibn Taimiyyah in the seventh rank in the hierarchy of the school of thought's authority and emphasized that Ibn Taimiyyah was not the only one bearing the title of sheikh al-Islamwithin the Hanbali school of thought.